High‐throughput, high‐accuracy determination of coefficient of thermal expansion of carbon fibre–epoxy composites using digital image correlation. (11th December 2017) - Dong, Y. L.; Zhang, Z. Y.; Pan, B.
Abstract: High‐throughput, high‐accuracy determination of thermal deformation and coefficient of thermal expansion (CTE) of carbon fibre–epoxy composites using 2D‐digital image correlation (2D‐DIC) is described. With the aid of a specially designed ultra‐stable and high fidelity imaging system, which integrates a high‐quality bilateral telecentric lens with monochromatic blue light illumination, surface images of multiple samples heated by a heating furnace can be captured simultaneously. The images of these samples at different temperatures are processed by advanced DIC algorithm to extract the thermal strains and the CTE of isotropic Al alloy, anisotropic unidirectional, and bidirectional carbon fibre–epoxy composites. Pure thermal expansions of these samples obtained after removing the small rigid‐body rotations clearly indicate the isotropic and anisotropic expansions of these samples. The well‐agreed results with literature values demonstrate the effectiveness and practicality of the proposed method for high‐throughput and high‐accuracy CTE measurements.